Cation Involvement in Telomestatin Binding to G-Quadruplex DNA. (23rd May 2010) - Rosu, Frédéric; Gabelica, Valérie; Smargiasso, Nicolas; Mazzucchelli, Gabriel; Shin-Ya, Kazuo; De Pauw, Edwin
Abstract : The binding mode of telomestatin to G-quadruplex DNA has been investigated using electrospray mass spectrometry, by detecting the intact complexes formed in ammonium acetate. The mass measurements show the incorporation of one extra ammonium ion in the telomestatin complexes. Experiments on telomestatin alone also show that the telomestatin alone is able to coordinate cations in a similar way as a crown ether. Finally, density functional theory calculations suggest that in the G-quadruplex-telomestatin complex, potassium or ammonium cations are located between the telomestatin and a G-quartet. This study underlines that monovalent cation coordination capabilities should be integrated in the rational design of G-quadruplex binding ligands.